Structure and energy of liquid foams - WEAIRE, DENIS; HUTZLER, STEFAN; HUTZLER, STEFAN; WEAIRE, DENIS LAWRENCE (My University, 2015)
We present an overview of recent advances in the understanding of foam structure and energy and their depen- dence on liquid volume fraction. We consider liquid foams in equilibrium for which the relevant energy is surface energy. Measurements of osmotic pressure can be used to determine this as a function of liquid fraction in good agreement with results from computer simulations. This approach is particularly useful in the description of foams with high liquid content, so-called wet foams. For such foams X-ray tomography proves to be an important technique inanalysing order and disorder. Muchof the discussion in this articleis alsorelevantto bi-liquid foams, i.e. emulsions, and to solid foams, provided that the solidi fi cation preserves the structure of the initially liquid foam template.
PUBLISHED
Keywords: Foam structure Emulsion structure Osmotic pressure Interfacial energy Jamming; Foam structure Emulsion structure Osmotic pressure Interfacial energy Jamming